Co‐creation of information materials within the assent process: From theory to practice - Jaime Fons‐Martinez; Cristina Ferrer‐Albero; Javier Diez‐Domingo (Wiley, 2023)
Abstract Introduction The informed consent process is key to safeguarding the autonomy of the participant in medical research. For this process to be valid, the information presented to the potential participant should meet their needs and be understood by them. The i‐CONSENT project has developed 'Guidelines for adapting the informed consent process in clinical trials' which aim to improve informed consent so that they are easier to understand and better adapted to the needs and preferences of the target population. The best way to tailor information to the characteristics and preferences of the target population is to involve the community itself. Methods Following guidelines developed by i‐CONSENT, assent materials were co‐created for a mock clinical trial of the human papillomavirus vaccine in adolescents. During the process, two design thinking sessions were conducted involving a total of 10 children and 5 parents. The objectives of the sessions were to find out the children's opinion of the informed consent (assent in their case) process in clinical trials, identify the parts that were most difficult to understand and alternatives for their presentation and wording, identify the preferred formats for receiving the information and the main characteristics of these formats, design a video explaining the clinical trial and evaluate a tool for assessing comprehension. Results Assent materials were co‐created in three formats: a web‐based material following a layered approach; a video in story format; a pdf document with an innovative way of presenting information compared to traditional assent documents. In addition, the Comprehension of Assent Questionnaire was co‐designed, based on the Quality of Informed Consent questionnaire. Conclusion The design thinking methodology has proven to be an easy and useful tool for involving children in designing information tailored to their needs and preferences. Patient or Public Contribution A sample of the target population participated in the design and piloting of the materials created using design thinking methodology. In addition, patient representatives participated in the design and evaluation of the guidelines developed by the i‐CONSENT project that were followed for the development of the materials in this study.